Clinical impact of patient‐centered care for hemodialysis patients using routine assessment of symptom burden. Issue 2 (7th July 2021) - Ito, Minoru; Nawano, Takaaki; Masakane, Ikuto; Yamaguchi, Ichiro; Kudo, Kenichi; Nagasawa, Junichiro; Yabuki, Kiyotaka
Abstract: The study aimed to verify the impact of our clinical strategy, which emphasizes patient‐centered care, based on patient‐reported outcome measures (PROMs) results in hemodialysis patients. We developed our original PROM (comprising 20 items) to assess patients' symptom burden. To confirm the validity of our clinical pattern, we performed various analyses using PROM data. We retrospectively enrolled 383 individuals (mean age 66.3 years; 252 men), collected their PROM data in December 2013, and followed them up for 3 years. We noted a lower mortality rate and a lower prevalence of itching in our facilities than in previous surveys and reports in Japan. Furthermore, we observed that the severity of symptom burden affected medium‐term prognosis. This is the first study to report the results of patient‐centered medical practice utilizing PROMs in dialysis care. Careful attention should be paid to patients' symptom burden, as performed in objective data management.